Seasonal changes in the assembly mechanisms structuring tropical fish communities. Issue 1 (16th December 2016) - Fitzgerald, Daniel B.; Winemiller, Kirk O.; Sabaj Pérez, Mark H.; Sousa, Leandro M.
Abstract: Despite growing interest in trait‐based approaches to community assembly, little attention has been given to seasonal variation in trait distribution patterns. Mobile animals can rapidly mediate influences of environmental factors and species interactions through dispersal, suggesting that the relative importance of different assembly mechanisms can vary over short time scales. This study analyzes seasonal changes in functional trait distributions of tropical fishes in the Xingu River, a major tributary of the Amazon with large predictable temporal variation in hydrologic conditions and species density. Comparison of observed functional diversity revealed that species within wet‐season assemblages were more functionally similar than those in dry‐season assemblages. Further, species within wet‐season assemblages were more similar than random expectations based on null model predictions. Higher functional richness within dry season communities is consistent with increased niche complementarity during the period when fish densities are highest and biotic interactions should be stronger; however, null model tests suggest that stochastic factors or a combination of assembly mechanisms influence dry‐season assemblages. These results demonstrate that the relative influence of community assembly mechanisms can vary seasonally in response to changing abiotic conditions, and suggest that studies attempting to infer a single dominant mechanism from functional patterns may overlook important aspects of the assembly process. During the prolonged flood pulse of the wet season, expanded habitat and lower densities of aquatic organisms likely reduce the influence of competition and predation. This temporal shift in the influence of different assembly mechanisms, rather than any single mechanism, may play a large role in maintaining the structure and diversity of tropical rivers and perhaps other dynamic and biodiverse systems.